Validation of the global allergy and asthma european network (GA2LEN) chamber for trials in allergy: innovation of a mobile allergen exposure chamber - Zuberbier, Torsten; Pfaar, Oliver (The journal of allergy and clinical immunology, 2017)
Background - Field clinical trials of pollen allergy are affected by the impossibility of predicting and determining individual allergen exposure because of many factors (eg, pollen season, atmospheric variations, pollutants, and lifestyles). Environmental exposure chambers, delivering a fixed amount of allergen in a controlled environmental setting, can overcome these limitations. Environmental exposure chambers are currently already used in phase 2, 3, and even 4 trials. Unfortunately, few chambers exist in the world, and this makes it difficult to perform large, multicenter clinical trials. The new Global Allergy and Asthma European Network (GA2LEN) mobile exposure chamber is a step forward because the mobility of the chamber makes it convenient for patients to participate in clinical testing. - Objective - This study was made to validate the reproducibility, sensitivity, and specificity of the results obtained in the new GA2LEN chamber. - Methods - Seventy-two adult patients (19-61 years old) with allergic rhinitis with or without asthma caused by grass pollen were included in different clinical validation tests. Total symptom scores and total nasal symptom scores were recorded at time zero (0) and every 10 minutes during exposures, along with nasal and respiratory parameters. - Results - Exposure tests confirmed the reproducibility between subsequent runs and the sensitivity (P < .00001 vs patients exposed to placebo) and specificity (very low score in nonallergic subjects) in the GA2LEN chamber. No adverse reactions were recorded during the tests. - Conclusions - The mobility of the GA2LEN chamber provides a new, potentially effective, and safe way of generating reliable data in allergy multicenter clinical trials.